Ринок туристичних послуг та поляризація туристичної системи - Трусова, Наталя Вікторівна; Трусова, Наталья Викторовна; Trusova, Natalia; Грановська, В. Г.; Крикунова, В. М. (My University, 2020)
UK: У статті розглядається ринок туристичних послуг, який визначає параметри сукупного значення субіндексів мезо- та місцевого рівнів та поляризацію туристичної системи. Комплексний підхід до оцінки концентрації сукупного значення індексу безпеки туристичної системи, який диференціюється за компонентами потенціалу безпеки та загроз, гарантує розвиток ринку туристичних послуг та модифікує туристичну систему на мезорівні в цілому. EN: The article deals with the development of the tourist services market, which determines the parameters of the aggregate value of the sub-indices of the meso- and local levels and polarization of the tourist system. The method-ology of spatial polarization of the tourist system, which provides convergence of the infrastructural space of tourist services, minimization of manifestation of destructive factors, balancing of interests of the country as a whole is substantiated. Has been proposed the scientific-methodical approach to the definition of the target landmarks for the development of the tourist services market, which implements polarized tourist space in terms of quantitative and qualitative parameters, makes it possible to analyze the destructive determinants of the periphery and determinants-producers of the tourist center of activity, evaluation and forecasting of the safe level of the hierarchy of the tourist system, determination of clear impulses for the development of the tourist services market and density of interaction of the periphery with the center. Revenues from the sale of tourist services of local level enterprises have been analyzed. The costs for the service of consumers of tourist services of subregions have been differentiated. The coefficients of localization and concentration of income from the sale of services are calculated depending on the intensity of development of potential of tourist enterprises. A comprehensive approach to the assessment of the concentration of the aggregate value of the security index of the tourist system, which is differentiated by the components of the security potential and threats, guarantees the development of the tourist services market and modifies the tourist system on the mesolevel as a whole.
Market of the tourist services and polarization of the tourist system
Keywords: туристичні доходи; туристичні витрати; туристичний продукт; інноваційний потенціал; індекс безпеки туристичної системи; tourism revenues; tourism expenditures; tourism product; innovation potential; security index of the tourist system